Ocenka parametrov strelkovoj podgotovlennosti i pokazatelej postural'noj ustojcivosti u biatlonistov, prochodjašcich podgotovku na etape soveršenstvovanija sportivnogo masterstva v biatlone - Zagursky, N. S.; Romanova, Y. S. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article presents the results of testing the shooting preparedness of biathletes and the indicators of the postural balance of biathletes in five regions of Russia undergoing training at the stage of sports improvement. The data obtained indicate the need for correction of methods for improving the stability of the system`s «shooter-weapon». A significant indicator in assessing the indicators characterizing the postural balance, in our opinion, can be the coefficient of a sharp change in the direction of movement. A study showed that girls have this indicator, as well as the quality of equilibrium is higher than that of boys.